How to Achieve Sufficient Endogenous Insulin Suppression in Euglycemic Clamps Assessing the Pharmacokinetics and Pharmacodynamics of Long-Acting Insulin Preparations Employing Healthy Volunteers - Liu, Hui; Li, Ting; Yu, Hongling; Li, Jiaqi; Tan, Huiwen; Yu, Yerong (Frontiers in Pharmacology, 2022)
The therapeutic effect of basal insulin analogs will be sustained at a rather low insulin level. When employing healthy volunteers to assess the pharmacokinetics (PK) and pharmacodynamics (PD) of long-acting insulin preparations by euglycemic clamp techniques, endogenous insulin cannot be ignored and sufficient endogenous insulin inhibition is crucial for the PD and/or PK assessment. This study aimed to explore a way to sufficiently inhibit endogenous insulin secretion. Healthy Chinese male and female volunteers were enrolled. After a subcutaneous injection of insulin glargine (IGlar) (LY2963016 or Lantus) (0.5 IU/kg), they underwent a manual euglycemic clamp for up to 24 h where the target blood glucose (BG) was set as 0.28 mmol/L below the individual’s baseline. Blood samples were collected for analysis of PK/PD and C-peptide. The subjects fell into two groups according to the reduction extent of postdose C-peptide from baseline. After matching for the dosage proportion of Lantus, there were 52 subjects in group A (C-peptide reduction<50%) and 26 in group B (C-peptide reduction≥50%), respectively. No significant difference was detected in age, body mass index, the proportion of Latus treatment and female participants. A lower basal BG was observed in group B compared to group A (4.35 ± 0.26 vs. 4.59 ± 0.22 mmol/L, p < 0.05). The clamp studies were all conducted with high quality (where BG was consistently maintained around the target and exhibited a low variety). The binary logistic regression analysis indicated low basal BG as an independent factor for the success of sufficient endogenous insulin suppression. In conclusion, setting a lower sub-baseline target BG (e.g., 10% instead of 5% below baseline) might be an approach to help achieve sufficient endogenous insulin suppression in euglycemic clamps with higher basal BG levels (e.g., beyond 4.60 mmol/L).